Polanyi in the European Single Market: The Re- Regulation of Insurance - Mabbett, Deborah (Economic Sociology: The European Electronic Newsletter, 2015)
This article discusses the difference between a social policy approach to the regulatory embedding of a market and a moral economy approach using the insurance case wherein the European Union's Court of Justice ruled that insurers may not discriminate on grounds of sex in identifying risks.
Keywords: Court of Justice of the European Union; insurance; lawsuits & claims; reembedding; regulation; social policy

Benjamin Cohen on global political order: when Keynes meets realism – and beyond - Guzzini, Stefano (Contexto Internacional, 2015)
This article analyses the trajectory of Benjamin J. Cohen's work by focusing on his ongoing concern with the nature and governance of world order. It does so by playing out his debt to realism and to Keynesianism. In a first moment, Cohen criticises the economic determinism of dependency scholarship, while turning to political realism, and then to possible Keynesian co-operation under anarchy: agents have the power to affect positive change. Later, Cohen the disillusioned Keynesian, watching how the possible reform of financial markets is marginalised by politicians and academics alike, shifts his analysis to more structural aspects of governance or rule that affect actors' preferences. I draw two conclusions. First, in this shift towards theorising the global political order away from steering capacity towards impersonal rule and bias, Cohen also questions the very setup of the theories with which we deal with that world – only to see that this very inspiration of original IPE is abandoned in the course of the ongoing ‘professionalisation' of IPE as practised in the United States. Second, his analysis seems to incorporate a warning. The underlying grand question is nothing less than the bargain between capitalism and liberal democracy as we know it, since the present system undermines equality before the law – money trumps equal political rights – and undermines democratic accountability. One of the main achievements of the post-war Keynesian turn was the reappropriation of political space from anti-democratic forces. Therefore, the decline of Keynesianism could provoke a Polanyian nightmare in which the ‘double movement' by which the laissez-faire is answered by moves to protect society does not strengthen democracies, as in earlier times of ‘embedded liberalism', but undermines them instead.
Keywords: COHEN, Benjamin J.; Keynesian economics; capitalism; dependency; embedded liberalism; global governance; international finance; international relations; political realism; securities markets; structural power

Polanyi, Hayek, and the Impossibility of Libertarian Ideal Theory - Lindsay, Peter (Polity, 2015)
In 1944, two seminal works of political and social theory appeared: F.A. Hayek's The Road to Serfdom and Karl Polanyi's The Great Transformation. Both works focused on society's spontaneous resistance to the 'marketization' of life. Yet, the authors arrived at opposite normative conclusions. This article attributes the normative distance to a methodological clash over the role and limits of normative theorizing in the concrete and sometimes uncooperative world of politics. This clash, in turn, illuminates recent debates about 'ideal' and 'non-ideal' theory, and suggests limits to the applicability of the former.
Keywords: Great Transformation, The (Book); HAYEK, Friedrich A. von (Friedrich August), 1899-1992; Road to Serfdom (book); free enterprise; free markets; ideal theory; laissez-faire; libertarian theory; non-ideal theory

Gellner’s genealogy of the open society: Biopolitics as fragment and remainder - Ryan, Kevin (Thesis Eleven, 2015)
A decade before Foucault began to work with the related concepts of biopolitics and biopower, Gellner posed a series of questions which are suggestive of a similar line of inquiry. Gellner did not pursue this strand of his thought as an historical sociologist however. Instead he packaged it into a functionalist account of how industrial society reproduces itself. In Gellner’s writings, biopolitics is both present and absent, like a redacted text. This is the focus of this article, which locates Gellner’s method of inquiry within a corpus of genealogical studies that includes the work of Polanyi, Weber and Foucault. What distinguishes Gellner is that the history he reconstructs is a story of achievement in the face of terrible historical odds, but this culminates in a normative genealogy that limits the scope for critical analysis. The article concludes by adopting an alternative – yet still Gellnerian – approach to the question of social reproduction, thereby using Gellner to critique Gellner.
Keywords: FOUCAULT, Michel, 1926-1984; GELLNER, Ernest; biopolitics; biopolitics (philosophy); biopower; genealogy; historical sociology; realism; social aspects

The Bioeconomy as Political Project: A Polanyian Analysis - Goven, Joanna; Pavone, Vincenzo (Science, Technology & Human Values, 2015)
The bioeconomy is becoming increasingly prominent in policy and scholarly literature, but critical examination of the concept is lacking. We argue that the bioeconomy should be understood as a political project, not simply or primarily as a technoscientific or economic one. We use a conceptual framework derived from the work of Karl Polanyi to elucidate the politically performative nature of the bioeconomy through an analysis of an influential Organization for Economic Cooperation and Development (OECD) initiative, The Bioeconomy to 2030. We argue that this initiative is a response to some of the most acute challenges facing the current neoliberal-capitalist accumulation regime, which seeks to protect and extend that regime, through both what it occludes and what it promotes. Rather than taking the bioeconomy as a description of some subset of economic activity, we regard it as a promissory construct that is meant to induce and facilitate some actions while deterring others; most explicitly, it is meant to bring about a particular set of political–institutional changes that will shape the parameters of possible future action. The bioeconomy concept highlights the potential dangers of failing to situate ethnographic examinations of horizontal micro-relations within a political–economic macro-context that enables and constrains. Scholarly work in science and technology studies and elsewhere that does not recognize the wider politics of the bioeconomy risks unintentionally contributing to the legitimation of this political project.
Keywords: bioeconomy; commodification; cooperation; economics; ethnographic analysis; futures; inequality; literature; markets/economies; neoliberalism; organization; politics

The Great Mindshift: Linking Forerunners of a New Sustainability Paradigm - Gopel, Maja (Brookings Inst Press, 2015)
Making sustainability a policy goal is one of the greatest challenges of the 21st century. Calls for a paradigm shift are becoming increasingly frequent and urgent. In fact, change toward a sustainable form of society seems to be more within reach than ever before. The mindset of people has changed in the course of economic and environmental crises. This publication presents the current scientific and practical approaches that shape and empower the process of change toward true sustainability. It also raises the question as to the new possibilities that may arise from linking these approaches.
Keywords: environmental policy; environmental science; global warming & climate change; public policy; science

The limits to China's non-interference foreign policy: pro-state interventionism and the rescaling of economic governance - Gonzalez-Vicente, Ruben (Australian Journal of International Affairs, 2015)
China's foreign policy has been long committed to a principle of non-interference in the internal affairs of sovereign countries. While one could easily point out past and present-day inconsistencies in its implementation, this article argues that defenders and critics of the principle both rely on a limited interpretation of ‘interference’ or ‘intervention’ based on an ideology of Westphalian sovereignty. Particularly problematic is the conceptual distinction between the ‘political’ or ‘diplomatic’, on the one hand, and the ‘economic’, on the other. As Polanyi's concept of embeddedness reminds us, markets, society and politics occur simultaneously, and can only act as discrete realms in epistemological abstractions. It is thus argued that non-interference is a semi-formal institution that governs China's diplomatic engagements and affects its economic activities. While the totality of China's interactions with the world has diverse and sometimes contradictory impacts on global governance, non-interference itself has apparent consequences for the rescaling of regional economic governance. Specifically, this article contends that Chinese non-interference results in the empowerment of political elites at national levels, and thus in the (re-)emergence of the nation state as a gatekeeper and facilitator of the advancement of capitalist enterprises. As a result, through non-intervention, China's foreign policy undermines supranational regulatory approaches and fosters state-based regional architectures.
Keywords: China; China - foreign relations; People's Republic of China; Westphalians - foreign countries; bilateralism; economic policy; embeddedness; foreign policy; non-interference; socioeconomic theory; supranationalism

The power of market fundamentalism: Karl Polanyi's critique - Gamble, Andrew (Cambridge Review of International Affairs, 2015)
Keywords: BLOCK, Fred; Power of Market Fundamentalism: Karl Polanyi's Critique, The (Book); SOMERS, Margaret R.; markets; nonfiction; review

Mutating Neoliberalism: The Promotion of Italian Investors in Slovakia before and after the Global Financial Crisis - Sellar, Christian; Pástor, Rudolf (International Journal of Urban & Regional Research, 2015)
In the context of the literature on 'actually existing neoliberalisms', this article analyzes the policies and services supporting Italian foreign direct investment (FDI) in Slovakia. It identifies a group of organizations, both Slovak and Italian, which shape and deliver neoliberal pro-FDI policies. By studying such an 'investment promotion community' (IPC) before and after the global financial crisis of 2009, and during Italy's prolonged crisis, this article shows both the persistence and adaptability of neoliberal policies and institutions. In so doing, it highlights some of the transnational flows underpinning the 'domestication' of neoliberalism in Slovakia. These findings support recent literature arguing that post-crisis neoliberalism can be interpreted as a stunted Polanyian double movement, in which the state has improved some of its regulatory functions but without questioning the overarching neoliberal principles. Specifically, it shows that FDI policies and the support of Italian investors rest upon a professional community that has not changed much since the 2009 crisis. This community played a crucial role in embedding neoliberal rationalities in Slovakia and supports the persistence of this ideology in the post-crisis environment.
Keywords: Bratislava; Italy; Košice; Kralovsky Chlmec; Slovakia; Slovakia - economic conditions; Slovakia - foreign economic relations; capitalists & financiers; double movement; financial crisis; foreign direct investment; foreign investments; global financial crisis, 2008-2009; neoliberalism

Toward a Sartrean Economics - Kail, Michel; Sobel, Richard (Rethinking Marxism, 2015)
Despite the absence of a systematic analysis of economics in Sartre's work, we argue that a Sartrean economics can indeed be said to exist, even if it is an economics that still awaits development. The status that Sartre accords to the concept of scarcity allows him to advance the critique of economism begun by Karl Polanyi, who, for his part, had been satisfied simply to challenge the reduction of economics to its formal definition. Scarcity, Sartre teaches us, should not be submitted to the process of instrumental reason but should be considered as a fact of human history. Economic analysis, meanwhile, should not be based solely on the theme of man's confrontation with a typically ungrateful nature but should rather be articulated through the concept of the world as elaborated in Sartrean philosophy.
Keywords: POLANYI, Karl, 1886-1964; SARTRE, Jean-Paul, 1905-1980; economic systems; economism; scarcity; world

The Limits of Transformation: Contemporary Applications of Karl Polanyi - England, Christopher (Journal of Australian Political Economy. Summer2015/16, Issue 76, 2015)
The article explores the conception of the Great Transformation (GT) by economic historian Karl Polanyi and its contemporary applications. Topics covered include the continued existence of free market fundamentalism as a prominent ideology and as a living political project, the persistence of free market utopianism, and Polanyi's genealogy of the market system. Also discussed are his conception of industrialism and his use of functionalist theory to build a unified image of the social system.
Keywords: economics; free enterprise; functionalism; industrialism; political economy; social systems; utopias

A Reversed Double Movement in Brazil: The (Controversial) Evolution of the Partido dos Trabalhadores' Education Policy since 1980 - Guedes-Neto, Joao Victor (Journal of International Studies, 2015)
Karl Polanyi identified a double movement which took place during the bourgeoisie hegemony when, instead of liberalism, it has made use of interventionism to perpetuate its domination over the working class. Several studies have tried to update his analysis by identifying the double movement nowadays. Nevertheless, the academia has not addressed the possibility of a reversed phenomenon where the working class would make use of liberalism to perpetuate itself in power. This paper aims at analyzing the Brazilian case where the Partido dos Trabalhadores, a proxy for the working class, has implemented pro-market policies in higher education. Whereas the party has not passed through structural reforms such as the British and German working class parties, it has drastically changed its approach to policy-making and campaigning since its origin in 1980. The study concludes that a reversed double movement may occur when the working class is in charge of the government.
Keywords: double movement; economic development; education; education: government policy; human development; human resources; income distribution; migration; national government expenditures and education

Contesting 'Actually Existing' Neoliberalism - Ryan, Matthew (Journal of Australian Political Economy, 2015)
The article explores the established conception of actually existing neoliberalism. Topics covered include free-market neoliberalism, the nature of neoliberal theory, and the distinction between esoteric and exoteric neoliberalisms. Also discussed are the ideas of scholars Karl Polanyi and Ha-Joon Chang about the role of the state in capitalist development, and scholar Damien Cahill's idea that neoliberalism is defined by microeconomic policies of privatization, marketization and deregulation.
Keywords: CAHILL, Damien; CHANG, Ha-Joon; esotericism; free enterprise; neoliberalism; political economy